Recent advancements in poly-Si/SiOx passivating contacts for high-efficiency silicon solar cells: technology review and perspectives. Issue 38 (12th September 2022) - Zhou, Jiakai; Su, Xianglin; Huang, Qian; Zhang, Bike; Yang, Jie; Zhao, Ying; Hou, Guofu
Abstract : The paper provides an outline of the present status in lab and industry of TOPCon structure. Additionally, this review discusses the remaining hurdles and the promise with the aim of providing guidance for the development of TOPCon solar cells. Abstract : As photovoltaics (PVs) made out of crystalline silicon (c-Si) have become more commonplace, the past decade has witnessed leaps and bounds in performance advances, the majority of which have been focused on lowering the losses associated with the directly metallized and/or heavily doped regions seen in typical devices. There are a number of recent developments that have the potential to greatly enhance the efficiencies of commercially available thin-film c-Si solar cells, including passivating contact featuring stacks of polysilicon (poly-Si)/SiO x, commonly abbreviated as TOPCon (tunnel oxide passivated contacts), which has led to efficiencies of over 26% and 24% being achieved by lab-based and industrial cells, respectively. This paper provides an outline of the evolution of this structure, which dates back to the 1980s, and a description of the present status of this technique in the lab and in industry. While the future of poly-Si junctions seems to be bright, as predicted by the International Technology Roadmap for Photovoltaics, various difficulties remain unresolved, such as the preparation of poly-Si and metallization issues. Additionally, this review discusses the remaining hurdles and the potential for poly-Si junctions to revolutionize the PV industry.